2018
DOI: 10.1080/2162402x.2018.1426518
|View full text |Cite
|
Sign up to set email alerts
|

Super-charged NK cells inhibit growth and progression of stem-like/poorly differentiated oral tumorsin vivoin humanized BLT mice; effect on tumor differentiation and response to chemotherapeutic drugs

Abstract: Therapeutic role of NK cells in solid tumors was challenged previously even though their role in hematological malignancies has clearly been established. Furthermore, functions and numbers of NK cells are greatly suppressed in oral cancer patients necessitating effective future NK immunotherapeutic strategies to aid in the control of disease. The humanized-BLT (hu-BLT) mice were used to implant stem-like/undifferentiated oral tumors to study the role of super-charged NK cells with and without feeding with AJ2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 38 publications
4
67
0
Order By: Relevance
“…In contrast, higher expression of CD44 on the tumor cells [20] and increased PD-1 expression in the peripheral blood of patients [19] was correlated with poor tumor differentiation and the aggressiveness of the tumors. In agreement, we have previously shown that increased MHC-class I, CD54, and PD-L1 expression on tumors is correlated with well-differentiated tumors and better prognosis in our in vitro and in vivo studies [22,23].…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, higher expression of CD44 on the tumor cells [20] and increased PD-1 expression in the peripheral blood of patients [19] was correlated with poor tumor differentiation and the aggressiveness of the tumors. In agreement, we have previously shown that increased MHC-class I, CD54, and PD-L1 expression on tumors is correlated with well-differentiated tumors and better prognosis in our in vitro and in vivo studies [22,23].…”
Section: Introductionsupporting
confidence: 92%
“…Similar to those seen with the pancreatic tumors, implantation of oral stem-like tumors in the oral cavity of hu-BLT mice resulted in similar profiles of cytotoxicity and secretion of IFN-γ from PBMCs isolated from oral tumor bearing mice in the presence and absence of NK injection (23).…”
Section: Suppression Of Nk Cell Cytotoxicity and Decreased Secretion supporting
confidence: 58%
See 2 more Smart Citations
“…124 On the other hand, adoptive transfer of NK cells can eliminate the cancer stem cell compartment making the tumour more differentiated and sensitive to chemotherapeutic drugs. 125,126 With regards to innovative therapies, proteasome inhibition, which reduces MHC class I molecules expression, have been shown to upregulate MICA/B and death receptors on several solid tumour CSCs, enhancing NK cell-mediated killing and tumour regression in vivo after NK cell adoptive transfer. 127 Another field of active research is the development of mAbs specifically targeting CSC surface markers.…”
Section: And Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%